2017
DOI: 10.1002/jbt.21947
|View full text |Cite
|
Sign up to set email alerts
|

TCDD induces UbcH7 expression and synphilin‐1 protein degradation in the mouse ventral midbrain

Abstract: UbcH7 is an ubiquitin-conjugating enzyme that interacts with parkin, an E3 ligase. The UbcH7-parkin complex promotes the ubiquitination and degradation of several proteins via the 26S proteasome. Cellular accumulation of the UbcH7-parkin targets alpha-synuclein and synphilin-1 has been associated with Parkinson disease. In mouse liver, 2,3,7,8-tetrachlorodibenzo-p-dioxin, an aryl hydrocarbon receptor ligand, induces UbcH7 expression. Therefore, the aim of the present study was to determine whether 2,3,7,8-tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…We previously reported that activation of AhR also results in UbcH7 induction together with a decrease in synphilin-1 (Sncaip) protein levels in the mouse ventral midbrain [16]. These data, together with those reported here, suggest that AhR-mediated increased Parkin and UbcH7 levels may be responsible for the decreased of both the O-linked glycosylated Snca and Sncaip protein levels.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We previously reported that activation of AhR also results in UbcH7 induction together with a decrease in synphilin-1 (Sncaip) protein levels in the mouse ventral midbrain [16]. These data, together with those reported here, suggest that AhR-mediated increased Parkin and UbcH7 levels may be responsible for the decreased of both the O-linked glycosylated Snca and Sncaip protein levels.…”
Section: Discussionsupporting
confidence: 85%
“…The aryl hydrocarbon receptor (AhR) mediates the expression of several genes encoding ubiquitin proteasome system proteins [14][15][16], in particular Ubch7 (also known as UBE2l3 in humans and UbcM4 in mice), an E2 ubiquitin enzyme partner of PRKN. AhR is a ligandactivated transcription factor that mediates the toxicity of environmental pollutants, and its highest-affinity ligand is 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD).…”
Section: Introductionmentioning
confidence: 99%
“…While genetics may play a role due to family history being a risk factor, the majority of cases are spontaneous, suggesting that there could be environmental triggers. There are several environmental neurotoxic compounds now thought to induce PD, including the heroin analog 1‐methyl‐4‐phenyl‐1, 2,3,6‐tetrahydropyridine (MPTP) and the herbicides paraquat and 2,3,7,8‐tetrachlorodibenzodioxin (TCDD) (Gonzalez‐Barbosa et al, ). Since PD patients share many aspects of cellular senescence including inflammation (Yan et al, ), oxidative stress (Dias, Junn, & Mouradian, ), and mitochondrial dysfunction (Jiang, Jiang, Zuo, & Gu, ) and astrocytes have been shown to senesce in response to various stressors, it has been proposed that astrocyte senescence in response to environmental toxins could be a contributor to PD (Chinta et al, ).…”
Section: Neurodegenerative Disease and Astrocyte Senescencementioning
confidence: 99%
“…The AHR has also been shown to mediate the expression of several genes encoding the protein components of the ubiquitin proteasome pathway, specifically, Ubch7, an E2 ubiquitin enzyme partner of parkin (PRKN) [81]. Parkin is an E3 ligase that catalyzes the ubiquitination of several proteins, including α-synuclein, synphilin-1, and Cdc-Rel, and plays a major role in the development of Parkinson's disease (PD), the second most common neurodegenerative disease [82][83][84].…”
Section: The Ahr and Non-ocular Neurodegenerative Diseasesmentioning
confidence: 99%